Influence of the use of biosynthesis inhibitor ethylene on the efficiency of combine harvesting - Dias, Rodrigo Elias Batista Almeida; Silva, Fábio Moreira da; Cunha, João Paulo Barreto; Avelar, Rogner Carvalho; Fernandes, Fernando Costa (Coffee Science - ISSN 1984-3909, 2014)
The mechanized harvesting is evolving daily and has become an increasing and irreversible process. However, one of the limitations of the harvest, either manual or mechanized, is the uneven ripening, which affects the operating performance and the product quality, resulting economic losses to producers. Thus, this study was carried out with the objective of evaluating the operation of the mechanized coffee harvesting using the inhibitor of ethylene biosynthesis, seeking to understand their influence on the natural fall. The study was conducted in Ouro Verde farm, located in Lavras-MG. The tests were conducted in the experimental area of 1.0 ha for Catuaí Vermelho IAC 15 in the years 2012 and 2013 and Acaiá Cerrado MG 1474 only in 2013, loading parameters were determined the plant load, maturation index, natural fruit fall and efficiency of mechanical harvesting . Based on the result obtained, the application of the inhibitor of ethylene biosynthesis at dosage of five liters per hectare showed greater efficiency in crop cultivar Catuai Vermelho IAC 15. The natural fruit fall decreased with the application of two dosage of ethylene inhibitor (5 + 5 liters per hectare) for the Acaiá Cerrado MG 1474 in the year 2013.